Polarity effect of pulsed corona discharge plasma on seed surface modification - Bunme, Pawita; Khamsen, Natthaporn; Kasemsuwan, Varakorn; Jitkajornwanich, Kulsawasd; Pichetjamroen, Achara; Teerakawanich, Nithiphat; Srisonphan, Siwapon (My University, 2017)
This paper presents an experimental analysis and underlying mechanism of positive and negative pulsed corona discharge induced atmospheric non-Thermal plasma. We designed a system based on point-plane configuration to produce direct corona discharge plasma (DCP) and hybrid corona discharge plasma (HCP) systems. The polarity effect of corona discharge for surface modification application on rice seeds was investigated under atmospheric dry air ambient. The reactive species under negative and positive corona discharge plasma were also studied for optimization design. The results show that only negative pulsed corona discharge is feasible for DCP system while both positive and negative pulsed corona discharge can be employed for in HCP system.
Keywords: Atmospheric non-Thermal plasma; Breakdown mechanism; Corona discharge; High voltage insulation; Surface modification